Long-term sustainability of response to upadacitinib among patients with active rheumatoid arthritis refractory to biological treatments: results up to 5 years from SELECT-BEYOND - Ronald F van Vollenhoven; Roy Fleischmann; Stephen Hall; Yanna Song; Sebastian Meerwein; Alvin F Wells; Oishi Tanjinatus (RMD Open)
Objective To evaluate the long-term sustainability of response to the Janus kinase inhibitor upadacitinib among patients with rheumatoid arthritis and an inadequate response or intolerance to biological disease-modifying antirheumatic drugs (bDMARD-IR) in the SELECT-BEYOND phase 3 trial.Methods Patients on background conventional synthetic DMARDs (csDMARDs) were treated once daily with upadacitinib 15 mg or placebo. Patients who completed the week 24 visit could enter a long-term extension of up to 5 years. The sustainability of response was assessed based on achievement of Clinical Disease Activity Index (CDAI), Simplified Disease Activity Index (SDAI) and Disease Activity Score 28-joint count using C-reactive protein (DAS28 (CRP)) targets and evaluated up to week 260 in all patients receiving the approved upadacitinib 15 mg dose, including those randomised to upadacitinib 15 mg and those who switched from placebo to upadacitinib 15 mg at week 12.Results In this bDMARD-IR population, 45% (n=104/229) and 79% (n=172/219) of patients treated with upadacitinib 15 mg plus background csDMARD(s) achieved CDAI remission or CDAI low disease activity (LDA) at any point during the 5-year study, respectively. Of those who achieved CDAI remission/LDA, 25%/43% maintained their initial response through 240 weeks of follow-up after first achieving response. Most patients who lost remission or LDA were able to recapture that response by the cut-off date. Similar overall results were observed for SDAI and DAS28 (CRP). No strong predictors of response were identified.Conclusions Over three-quarters of bDMARD-IR patients achieved CDAI LDA with upadacitinib, and almost half of those maintained LDA through 240 weeks of follow-up. Remission was achieved by nearly half of all patients and maintained in approximately a quarter of those achieving remission.Trial registration number NCT02706847.